Enhancing Online Customer Engagement for Zhang Yiyuan Tea Products: An Analysis of Convenience, User-Friendliness, Customer Support, and Security Assurance in the Online Purchase Process - haoran zhao; Nuttawut Rojniruttikul (My University, 2023)
This research study investigates the determinants of online customer engagement for Zhang Yiyuan tea products within the e-commerce context. The primary objective is to gain an in-depth understanding of how various factors, namely convenience of online purchase, user-friendliness of the online platform, customer support, and security and privacy assurance, influence online customer engagement. Utilizing a quantitative research approach, the study collected data from 385 respondents who have prior experience with online purchases of Zhang Yiyuan tea products, employing convenience sampling to select customers.
Keywords: Digital Marketing and Social Media; Customer Service Quality and Loyalty; Technology Adoption and User Behaviour